Contribution of MEK1/ERK1/2/iNOS Pathway to Oxidative Stress and Decreased Caspase-3 Activity in Endotoxemic Rats - Korkmaz, Belma; Cuez, Tuba; Kemal Buharalioglu, C.; T. Demiryurek, Abdullah; Sahan-Firat, Seyhan; Nihal Sari, A.; Tunctan, Bahar (Anti-Inflammatory & Anti-Allergy Agents in Medicinal Chemistry, 2012)
Oxidative stress and apoptosis are the states that can contribute to the pathogenesis of sepsis. In this study we aimed to investigate whether mitogen-activated protein kinase kinase 1 (MEK1)/extracellular signal-regulated kinase 1/2 (ERK1/2)/inducible nitric oxide synthase (iNOS) pathway plays a role in oxidative stress and apoptosis in endotoxemic rats. Systemic total antioxidant, SOD, GPx, and GR activities as markers of oxidative stress, and tissue caspase-3 enzyme activity as a marker of apoptosis were measured in sera and thoracic aortae of male Wistar rats sacrificed 4 h after being treated with saline (vehicle) or lipopolysaccharide (LPS) (10 mg/kg, i.p.). A decrease in total antioxidant activity and caspase-3, SOD, GPx, and GR enzyme activities was occured by LPS. These changes caused by LPS were prevented when a selective iNOS inhibitor, 1,3-PBIT (10 mg/kg, i.p.) or a selective inhibitor of ERK1/2 phosphorylation by MEK1, U0126 (5 mg/kg, i.p.) were given 1 h after administration of LPS. Our results suggest that decreased activity of MEK1/ERK1/2/iNOS pathway prevents oxidative stress by increasing systemic antioxidant enzyme activities and restores decreased caspase-3 activity in thoracic aorta in endotoxemic rat.
Keywords: oxidative stress